Interventions for teaching sketching skills and reducing inhibition for novice engineering designers. (March 2016) - Booth, Joran W.; Taborda, Elkin A.; Ramani, Karthik; Reid, Tahira
Abstract : This paper explores improving sketching skills and reducing the inhibition to sketch for student designers. In the first study, students were taught sketching skills through an in-class workshop. The effect was evaluated using a pre-mid-post test ( n = 40). In the second study, students were led through art activities to reduce their inhibition to sketch. The effect was tested using another pre-mid-post test ( n = 26). The first study found sketching skills increased, but declined with disuse. The second study found reduced inhibition immediately after the workshop, an increase after the sketch skills workshop, and a decrease over the semester. This suggests that sketch training and inhibition-reducing exercises are effective in the short term, but must be emphasized over time for a permanent change. Highlights: We found that engineering students are reluctant to sketch. We propose 1) a training workshop to teach sketching skills to engineers. We propose 2) an art-based workshop to reduce student inhibition to sketch. We found that the workshops are effective, but require long-term practice. Advanced sketch skills (e.g. perspective) can temporarily increase inhibition.